Metal ions-bridged J-aggregation mediated nanoassembly composition for breast cancer phototherapy - Chen Chen; Shan Yang; Yufei Liu; Yue Qiu; Jing Yao (Elsevier, 2022)
Recently, the highly ordered J-aggregates of organic dyes with intriguing optical properties have received considerable attention in biomedical applications. Herein, binary metal ions Mn(II)/Fe(III) are used to induce the formation of indocyanine green (ICG) J-aggregates. Further, the sheet-like J-aggregates are able to act as ''carriers'' for loading hydrophobic chemotherapeutic gambogic acid (GA), realizing the effect of ''killing two birds with one stone'' for both treatment and delivery. The as-designed nanoassembly is formed spontaneously in aqueous environment via π-π stacking, electrostatic interaction, and hydrophobic force, exhibiting enhanced photostability of ICG and outstanding reactive oxygen species (ROS) generation ability. Moreover, significant inhibition of tumor growth by the synergetic effect of phototherapy and chemotherapy is verified in a subcutaneous 4T1 tumors model. In conclusion, this work not only presents a facile and green approach to manufacture carrier-free nanodrugs, but also establishes a universal platform that has potential application in the co-delivery of near-infrared dye and hydrophobic molecules.